An Integrated Practical Evidence-Based Medicine Curriculum, Critical Appraisal: Diagnostic Test - Maribeth Chitkara; Rachel Boykan; Catherine Messina (Association of American Medical Colleges, 2014)
Abstract Introduction The need to teach evidence-based medicine (EBM) goes beyond meeting the requirements of residency. For residents and all practicing physicians there must be a process to ensure that doctors know the latest and best information to apply to the care of their patients. Typically, in the majority of pediatric training programs, EBM is taught in the context of a journal club, which may not develop the skills needed to integrate EBM into one's own clinical practice. Therefore, we created this 1-hour small-group session on diagnostic tests. Methods In this 1-hour session, residents are re-introduced to basic EBM principles and given instruction regarding the appraisal of an article about a diagnostic test. Guided practice both during and after the sessions reinforces skills learned. While the curriculum was designed for and has been studied on pediatric residents, it could easily be adapted for use by a broader audience including residents of any specialty, and medical students in their last 2 years of medical school. Results Participants were evaluated using a quiz comprised of true/false, matching, and multiple-choice questions prior to the initiation and at the completion of all small-group sessions. Evaluation of the first two cohorts of residents participating in our curriculum revealed overall improvement in EBM knowledge. Discussion There is an increasingly large body of medical literature available to practicing physicians. Ideally this allows medical practitioners to change their practice as medical knowledge evolves. Rather than memorizing facts and creating ingrained habits, medical residents and students in training must learn to be flexible in their clinical approach, integrating best evidence as it becomes available.